BAD NUTRITION FACTORS IN THE COASTAL COASTAL BEACH - Hati Baculu, Eka Prasetia; Jufri, Muhammad (PROMOTIF: Jurnal Kesehatan Masyarakat, 2017)
Malnutrition or acute malnutrition is the most severe form of chronic malnutrition, the presence or absence of oedeme or weight per age <-3 SD according to WHO growth standards. Malnutrition affects physical growth, morbidity, mortality, cognitive development, reproduction, and physical work capacity and its impact on human performance, and health. This study aims to determine risk factors in underfive children. Type of case control research. Malei Health Center Sub District Balaesang Tanjung. The study began in January 2017. Sampling technique with total sampling according to inclusion and exclusion criteria were 56 samples consisting of case and control. The result of bivariate analysis showed the level of energy intake (OR = 3,84, 95% CI 0,68-21,51), protein intake level (OR = 4,94; 95% CI 0,50-48,29) and history of disease infection (OR = 2.13; 95% CI 0.61-7.32) was significantly associated with poor nutrition. Low Birth Weight indicates the level of protein intake has a strong relationship with the risk of malnutrition. The level of energy intake, the level of protein intake and infectious diseases is a nutritional risk factor in infants.Â Keywords : Underfive Children, Risk Factor, MalnutritionÂ Â